An analysis of RTK network LitPOS performance - Baniulis, Rimvydas; Galinauskas, Karolis; Marozas, Leonardas; Paršeliūnas, Eimuntas; Petniūnas, Marius (International Conference “Environmental Engineering”, 2017)
RTK (Real Time Kinematic) method for positioning is used in daily life by different consumers for many purposes. When there are so many measurements, it is essential to know where RTK measurements are concentrated and which stations are obligatory for LitPOS performance. In this paper, using RTK software generated reports and SQL database records, we introduced the geographic information systems show to graphically LitPOS users activity and density of measurements. Using this data we analyze how LitPOS users are divided among Lithuanian municipalities, how much users are working each month and how this affects LitPOS performance. This study is performed in Lithuania, where state wide permanent GNSS reference station network has been maintained since year 2007.
Keywords: GNSS; CORS Network; LitPOS; Real Time Kinematic; geodetic coordinate accuracy